ANALYSIS OF STUDENT’S LANGUAGE STYLE USING MARTIN JOOS THEORY AT ENGLISH EDUCATION DEPARTMENT - Maharani Illiyyin Zahra; Aridah; Ventje Jany Kalukar; Maria Teodora Ping; Iwan Setiawan (Universitas Duta Bangsa Surakarta, 2025)
In human society, the need for interpersonal connection has given rise to the emergence of language. Beyond serving as a medium of communication, language functions as a vehicle for articulating emotions and conveying thoughts, with its use shaped by contextual and situational factors. This research seeks to examine the language styles engaged by students of the English Education Department at Mulawarman University, using Martin Joos’ (1976) theory and Holmes (2013) as sociolinguistic theory. The study investigates the categories of language styles used in students' speech and the factors influencing their choice of style. A qualitative method was applied, utilizing data from a recorded video interview and follow-up semi-structured interviews with two selected participants. Data analysis was undertaken using thematic analysis guided by Braun and Clarke (2006) framework. The findings reveal that three out of five language styles formulated by Joos—consultative, casual, and intimate—were used by the participants, with consultative style being the most dominant. Language style occurred primarily in academic contexts, especially when interacting with instructors or unfamiliar individuals. Factors influencing language style include the speaker, setting, topic, and function, in alignment with Holmes’ (1992) sociolinguistic theory. Furthermore, although participants often identified their style as “formal,” triangulation with Joos’ and Braund and Clarke theory revealed that their usage aligned as consultative features. These findings provide valuable insights into how language styles function in educational settings and highlight the importance of context in language use.